2014
DOI: 10.1556/aoecon.64.2014.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Is there a trade-off between the predictive power and the interpretability of bankruptcy models? The case of the first Hungarian bankruptcy prediction model

Abstract: In our work, we compare the predictive power of different bankruptcy prediction models built on financial indicators calculable from businesses’ accounting data on the database of the first Hungarian bankruptcy model. For modelling, we use data-mining methods often applied in bankruptcy prediction: neural networks (NN), support vector machines (SVM) and the rough set theory (RST) capable of rule-based classification. The point of departure for our comparative analysis is the practical finding that black-box-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
1
19
0
4
Order By: Relevance
“…The results were comparable to those obtained by Virág and Kristóf, i.e., models of neural networks proved to be better, and among them the one with two layers was exceptionally superior. In subsequent studies, using the same learning sample from the years 1990-1991, Virág and Kristóf (2014) built models using the techniques of support vector machines and rough set theory. Based on the validation sample it was found that both models generated efficiencies similar to the one of the model developed using artificial neural networks.…”
Section: Hungarymentioning
confidence: 99%
“…The results were comparable to those obtained by Virág and Kristóf, i.e., models of neural networks proved to be better, and among them the one with two layers was exceptionally superior. In subsequent studies, using the same learning sample from the years 1990-1991, Virág and Kristóf (2014) built models using the techniques of support vector machines and rough set theory. Based on the validation sample it was found that both models generated efficiencies similar to the one of the model developed using artificial neural networks.…”
Section: Hungarymentioning
confidence: 99%
“…In addition, some authors have investigated the applicability of other artificial intelligence methods to bankruptcy prediction, for example, the principal component analysis [16,17], support vector machines [18,19], decision trees [20,21], rough sets, [12,22], data envelopment analysis [23,24], and others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Néhány önké-nyesen kiragadott példa a teljesség igénye nélkül: Virág -Hajdu (2001), Virág -Kristóf (2005), , Bozsik (2010), Virág -Nyitrai (2013), Virág -Nyitrai (2014). Találhatók azonban olyan tanulmányok is, amelyek egyértelműen rögzítik, hogy a kérdéses mutatók esetén a stock adatokat átlagolva vették figyelembe.…”
Section: Stock éS Flow Adatok a Pénzügyi Mutatószámokbanunclassified